Analisis Kualitatif Pemecahan Masalah dan Ketergantungan Kognitif Mahasiswa Calon Guru dalam Penggunaan Generative AI - Ferdinanda, Thierry; Dewi, Tiara Anggia; Budiono, Desi (Universitas Nusantara PGRI Kediri, 2026)
This qualitative descriptive study analyzes Generative Artificial Intelligence (GenAI) usage patterns and their impact on pre-service teachers' problem-solving capabilities through Polya’s framework. Data from ten informants were analyzed using the Miles and Huberman model. Findings reveal that GenAI serves as effective